Методы обучения и важнейшие факторы повышения эффективности качества образования - Фоменко, И.В. (My University, 2016)
The article is devoted to the issue date of the general education about the procedures and technologies novelty in teaching. The aim of the article is to reveal the content of the concept of active and effective means of comprehensive development of the individual. Practical experience of effective methods and techniques is generalized in the formation of creative abilities. The author concludes that the children should be taught to create by giving them the necessary knowledge and experience
Keywords: Self-realization; motiwation; active Creative activity